Digital compression of audio signals applying perceptual criteria and backward adaptation - Rodrigues, João Manuel de Oliveira e Silva (1999)
In this work, the problem of digital coding of high quality audio signals is analised, and the principies of perceptual coding are identified as the most satisfactory solution. We present a synthesis of the perceptual coding systems found in the literuture, stressing their common structure, and we characterize the possible variants that each module in that structure allows. Based on this study, a new perceptual audio coding system was developed. (...)